Changes in hematological manifestations in children with vivax malaria - Mangla, Ankit; Goel, Atul; Singh, Tejinder (International Journal of Contemporary Pediatrics, 2017)
Background: Malaria, especially Plasmodium falciparum is commonly associated with haematological abnormalities like anemia and thrombocytopenia. Vivax malaria, on the other hand was usually considered as a relatively benign illness. However over last decade or two, it is being increasingly realized that the vivax malaria is not a benign illness anymore. There have been number of reports and case series demonstrating severe haematological and clinical manifestations associated with vivax malaria mono-infection. Methods: The study group consisted of 132 cases of vivax mono-infection diagnosed on thick and thin blood smear examination, which were recorded from the retrospective data starting from June 2002 to December 2011 and the prospective part of study from January 2012 to July 2013. Results: Thrombocytopenia was the most common haematological manifestation in vivax malaria and has seen a significant increase from 62.9% to 87.2% from time period A to C. The proportion of children with anaemia in vivax malaria has increased from 69.4% in time period A to 78.6%. The incidence of leucocytopenia was seen in 25% cases of vivax monoinfection, with no significant change being observed over different time periods when compared among cases of vivax malaria. Conclusions: Vivax malaria was observed to be increasingly associated with thrombocytopenia and anemia over last decade.